1994
DOI: 10.1007/bf01371333
|View full text |Cite
|
Sign up to set email alerts
|

Serological findings and efficiency of DNA profiling in transfused patients and their significance for identity and paternity tests

Abstract: The problems of testing patients or the deceased using classical blood group systems for identity or paternity purposes after multiple transfusions are well known. In a paternity case where the putative father received multiple transfusions it was possible to determine some classical blood group systems. The investigation showed no incompatibility between the putative father and the child and led to a probability of paternity of 72.33%. Using the DNA technique (single locus probes) it could be demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…These facts supports our earlier findings that the DNA patterns generated by RFLP and PCR-based HLA-DQA1 and polymarker from recipients are not influenced by blood transfusion using whole blood 10 and packed red blood cell containing few leukocytes. 4,[7][8][9] Our results indicate that the male donorÕs DNA is not detectable even on using sensitive primer for STRs and Y-chromosome microsatellite marker in a transfused female. On the other hand Sahota et al 12 reported detection of 0.1% of male DNA against a background of female DNA using primers for the Ychromosome microsatellite marker, but the sensitivity increased up to 0.0001% using nested primers and similarly D1S80 minisatellite locus has been reported as a useful marker for detecting microchimerism with a sensitivity of 0.1%.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These facts supports our earlier findings that the DNA patterns generated by RFLP and PCR-based HLA-DQA1 and polymarker from recipients are not influenced by blood transfusion using whole blood 10 and packed red blood cell containing few leukocytes. 4,[7][8][9] Our results indicate that the male donorÕs DNA is not detectable even on using sensitive primer for STRs and Y-chromosome microsatellite marker in a transfused female. On the other hand Sahota et al 12 reported detection of 0.1% of male DNA against a background of female DNA using primers for the Ychromosome microsatellite marker, but the sensitivity increased up to 0.0001% using nested primers and similarly D1S80 minisatellite locus has been reported as a useful marker for detecting microchimerism with a sensitivity of 0.1%.…”
Section: Discussionmentioning
confidence: 92%
“…11,12 Already blood transfusion has featured in a few cases concerned with forensic and paternity identification. [5][6][7] Information regarding typing of DNA of recipient blood, after unfiltered whole blood transfusion is negligible. The use of DNA evidence in a court of law has increased since its origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature identifies that previous authors have shown that blood transfusion does not affect the DNA profiling of living or dead individuals from blood. A summary of the literature is presented in Table 1 [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%